MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI PERKEMBANGBIAKAN TUMBUHAN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH - Hesti Lestari; Dudung Suryana; Rizki Hadiwijaya Zulkarnaen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research was motivated by the low cognitive learning outcomes of fourth-grade students in Natural and Social Sciences at SDN 3 Jahiang. This is due to the use of a less varied learning model, resulting in students being passive and not fully understanding the material. The purpose of this study is to enhance students' cognitive learning outcomes by applying the Make a Match cooperative learning model. This study is a Classroom Action Research (CAR) project conducted in two cycles, involving 27 fourth-grade students from SDN 3 Jahiang as participants. Each cycle follows the stages of the Kemmis and McTaggart CAR model, which consists of planning, implementation, observation, and reflection. The data collection techniques employed were tests, observation, and documentation. The study's results showed an increase in students' cognitive learning outcomes following the implementation of the Make a Match cooperative learning model. In the pre-action phase, the average student score was 53.51 (classified as "Poor"), with a learning completion rate of 22.22%. In cycle I, the average score increased to 67.66 (category "Sufficient"), with a learning completion percentage of 55.56%. Furthermore, in cycle II, the average score increased again to 83.96 (category "Good"), with a learning completion percentage of 85.19%. Thus, the Make a Match cooperative learning model has been proven successful in improving students' cognitive learning outcomes in the topic of plant propagation.